Rekrutmen Calon Kepala Daerah dalam Era Pilkada Langsung dan Serentak di Kabupaten Musi Banyuasin - Ainur Ropik; Alva Beriansyah; Wijaya Wijaya (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2018)
The era of direct and simultaneous regional head elections makes political parties really have to pay attention to the regional head candidates who will be promoted. The candidate factor has a very big role in determining the victory in the elections. On Musi Banyuasin regional election in 2017 there is one pair of regional head candidates carried by all existing political parties. One of the parties that participated in carrying out the regional head candidates was PAN (Partai Amanat Nasional or National Mandate Party). However, regional head candidates who are carried by PAN are not PAN cadres. PAN is the party that won the election in 2014 and is the only party that can support its own regional head candidates. Determination of candidates for regional head by PAN is done through open recruitment. Open recruitment is carried out by the DPD (Dewan Perwakilan Daerah or Regional Representative Council) PAN Musi Banyuasin Regency by forming a selection committee. The selection committee is tasked with selecting prospective regional heads. The selection process is done by opening a registration. Registration is done by completing the registration form and fulfilling the registration requirements. The mechanism for determining prospective regional heads is proposed by conducting regional deliberations. The reference used in determining the prospective regional head to be carried out is an analysis of the nomination registration requirements, Second, the electability and popularity surveys and the Third is result of the fit and proper test. Candidates for the elected regional head will be proposed to the DPW (Dewan Pimpinan Wilayah or Regional Leadership Council), the DPW will proceed to the DPP (Dewan Pimpinan Pusat or Central Board), then the DPP will issue a recommendation that is used as a requirement in registering at the KPUD (Komisi Pemilihan Umum Daerah or Election Commission).